Clean agile : back to basics - Martin, Robert C. (Robert C. Martin series., 2020)
Agile Values and Principles for a New Generation "In the journey to all things Agile, Uncle Bob has been there, done that, and has the both the t-shirt and the scars to show for it. This delightful book is part history, part personal stories, and all wisdom. If you want to understand what Agile is and how it came to be, this is the book for you."--Grady Booch "Bob's frustration colors every sentence of Clean Agile, but it's a justified frustration. What is in the world of Agile development is nothing compared to what could be. This book is Bob's perspective on what to focus on to get to that 'what could be.' And he's been there, so it's worth listening." -Kent Beck "It's good to read Uncle Bob's take on Agile. Whether just beginning, or a seasoned Agilista, you would do well to read this book. I agree with almost all of it. It's just some of the parts make me realize my own shortcomings, darn it. It made me double-check our code coverage (85.09%)." -Jon Kern Nearly twenty years after the Agile Manifesto was first presented, the legendary Robert C. Martin ("Uncle Bob") reintroduces Agile values and principles for a new generation-programmers and nonprogrammers alike. Martin, author of Clean Code and other highly influential software development guides, was there at Agile's founding. Now, in Clean Agile: Back to Basics, he strips away misunderstandings and distractions that over the years have made it harder to use Agile than was originally intended. Martin describes what Agile is in no uncertain terms: a small discipline that helps small teams manage small projects ... with huge implications because every big project is comprised of many small projects. Drawing on his fifty years' experience with projects of every conceivable type, he shows how Agile can help you bring true professionalism to software development. Get back to the basics-what Agile is, was, and should always be Understand the origins, and proper practice, of SCRUM Master essential business-facing Agile practices, from small releases and acceptance tests to whole-team communication Explore Agile team members' relationships with each other, and with their product Rediscover indispensable Agile technical practices: TDD, refactoring, simple design, and pair programming Understand the central roles values and craftsmanship play in your Agile team's success If you want Agile's true benefits, there are no shortcuts: You need to do Agile right. Clean Agile: Back to Basics will show yo ...